A Comparative Assessment of Indicators for Public Sector General Insurance Companies : An Indian Perspective - Sarangi, Subrat; Kar, Brajaballav (Indian Journal of Finance, 2018)
Academic research in the insurance sector is limited to the life insurance segment with non-life insurance being an under focus area. This paper addressed the void in literature by studying the general insurance sector by comparing the performance from an Indian perspective. The research was based on studying all the major companies operating in the general insurance sector in India focusing on the critical dimensions of premiums collected by the insurance companies, claims paidÂ to the insured, and commissions paid to sales agents. As the Indian market is led by public sector companies, all the four major general insurance companies were researched, and a comparative assessment was made across two different geographic markets. The objective of the paper was not only to establish the linkages for firm performance across geographic markets, but also to identify a set of themes for future research to strengthen the body of literature on general insurance industry in India. The paper would have far reaching influence for general insurance practitioners too by providing the nuances of performance on relevant dimensions in the general insurance domain.